Analisis Manajemen UMKM Wanita (Studi Kasus pada UMKM Brambang Goreng Mongah-Mongah Sambal dan Bagor Classic di Desa Genengadal Kecamatan Toroh Kabupaten Grobogan - Lestari, Rina Mega; Kusumantoro, Kusumantoro (Universitas Negeri Semarang, 2023)
This study aims to determine financial management, marketing management and human resource management (MSDM) in UMKM Brambang Goreng Mongah-mongah Sambal and Bagor Classic. This study used a qualitative approach with data collection techniques, namely observation, interviews and documentation. The data analysis method used is the Milles and Huberman model analysis which includes data reduction, data display (presentation of data), drawing conclusions (verification). The results of the study show that good financial management can help business founders monitor and control incoming and outgoing cash flows in the Brambang Goreng UMKM. The marketing management used is based on the marketing mix including product, price, place and promotion which can increase the number of customers and revenue. Human resource management (HRM) aims to improve the quality of employees. The conclusions of this study, financial management, marketing management and human resource management (MSDM) are important factors that can increase the income of women in Genengada village in Brambang Goreng SMEs. In order to increase business success, women need to strengthen their capacities in managing finances, developing innovative and sustainable marketing management and human resources.